Advanced technologies for industry - Van de Velde, Els,Kretz, Daniela,Izsak, Kincsö (European Commission, 2020)
This sectoral report has been prepared in the framework of the 'Advanced Technologies for Industry' (ATI) project, initiated by the European Commission, Directorate General for Internal Market, Industry, Entrepreneurship and SMEs and the Executive Agency for Small and Medium-sized Enterprises. It analyses trends in the generation and uptake of advanced technologies, related entrepreneurial activities and skills needs in the agri-food sector with a specific emphasis on Industrial Biotechnology, Robotics, Big Data and Internet of Things (including e-commerce and app design). It interprets data from a list of data sources compiled to monitor advanced technologies and their applications in industry across Europe and key competitor economies. The starting point of this analysis has been 16 advanced technologies that are a priority for European industrial policy and that enable process, product and service innovation throughout the economy and hence foster industrial modernisation. Advanced technologies are defined as recent or future technologies that are expected to substantially alter the business and social environment and include advanced materials, advanced manufacturing, artificial intelligence (AI), augmented and virtual reality, big data, blockchain, cloud technologies, connectivity, industrial biotechnology, Internet of Things (IoT), micro and nanoelectronics, IT for mobility, nanotechnology, photonics, robotics, security. The relevance of these specific technologies in the agri-food industry has been explored through patent analysis and data on private equity investments, skills and technology uptake. The full methodology behind the data calculations is available here: https://ati.ec.europa.eu. This report is structured as follows: - The first section sets the industrial context. - The second section analyses technological trends in advanced technologies applied in the agrifood industry based on patents and text-mining of company websites. - The third section presents findings about private equity investment and startup/spinoff activity. - The fourth section explores the supply and demand of skills related to advanced technologies in the agri-food industry. - The fifth section concludes with a short future outlook.
10.2826/708050
Keywords: Graue Literatur; Technischer Fortschritt; Agroindustrie; EU-Staaten; new technology; agro-industry; biotechnology; robotics; big data; Internet of Things; innovation; industrial policy; nanotechnology; Internet site; investment; report